2021
DOI: 10.1016/j.biomaterials.2020.120431
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant-pulsed mRNA vaccine nanoparticle for immunoprophylactic and therapeutic tumor suppression in mice

Abstract: Synthetic mRNA represents an exciting cancer vaccine technology to the implementation of effective cancer immunotherapy. However, inefficient in vivo mRNA delivery along with a requirement for immune co-stimulation present major hurdles to achieving anti-tumor therapeutic efficacy. Here, we demonstrate a proof-of-concept adjuvant-pulsed mRNA vaccine nanoparticle (NP) that is composed of an ovalbumin-coded mRNA and a palmitic acid-modified TLR7/8 agonist R848 (C16-R848), coated with a lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(135 citation statements)
references
References 78 publications
1
116
0
Order By: Relevance
“…Recently, Islam et al demonstrated that mRNA vaccine pulsed with R848 adjuvant exhibits the anti-tumor efficacy in syngeneic mouse models of prostate cancer. 47 Our data prove that PLGA-ICG-R848 induced the significant maturation of BMDCs, and its combination with laser ablation increased the proportion of splenic NK cells, which may further contribute to a stronger anticancer efficacy against PCa. Further studies to evaluate the anti-metastasis effect and long-term maintenance of immunological memory against PCa are also required to better understand the therapeutic potential of PLGA-ICG-R848 NPs with NIR laser.…”
Section: Discussionsupporting
confidence: 63%
“…Recently, Islam et al demonstrated that mRNA vaccine pulsed with R848 adjuvant exhibits the anti-tumor efficacy in syngeneic mouse models of prostate cancer. 47 Our data prove that PLGA-ICG-R848 induced the significant maturation of BMDCs, and its combination with laser ablation increased the proportion of splenic NK cells, which may further contribute to a stronger anticancer efficacy against PCa. Further studies to evaluate the anti-metastasis effect and long-term maintenance of immunological memory against PCa are also required to better understand the therapeutic potential of PLGA-ICG-R848 NPs with NIR laser.…”
Section: Discussionsupporting
confidence: 63%
“…Other studies indicated that enhanced immune responses via combination with alternative adjuvants are required for mRNA vaccines to achieve the targeted anti-tumor therapeutic outcome and improved patients’ survival. Islam and coworkers have reported mRNA pulsed with a palmitic acid-modified TLR7/8 agonist R484 markedly improved the MHC class I presentation of OVA mRNA derived antigen in APCs, subsequently induced a more effective adaptive immune response in a tumor bearing mouse model as compared to mRNA vaccine without the adjuvant [ 55 ]. Moreover, the RNActiveÂź vaccine platform developed by CureVac AG.…”
Section: Strategies To Improve Mrna Translation Efficiency and Overcomentioning
confidence: 99%
“…Islam and coworkers utilized a modified PAMAM dendrimers, PLGA and ceramide PEG to formulate polymer-lipid hybrid nanoparticles to deliver phosphate and tensin homolog mRNA in vivo [ 114 ]. In a later study, they utilized the same vehicle to deliver OVA mRNA vaccine together with a fatty acid modified TLR7/8 agonist C16-R848, and showed the combination formulation could boost a strong antitumor immunogenicity [ 55 ].…”
Section: Delivery Of Mrna Cancer Vaccinementioning
confidence: 99%
See 1 more Smart Citation
“…mRNA encoding the tumor antigen TRP2, transfected using a formulation which contained the TLR–agonist LPS, resulted in prolonged survival in a B16F10 melanoma model 123 . Similar strategies, combining mRNA to other TLR agonists, like the small molecule R848, have also been proposed 124 .…”
Section: The Adaptive Immunitymentioning
confidence: 99%